Mengembangkan Pola Pikir Digital dan Keterampilan Lunak Melalui Program Mentoring yang Berpusat pada Manusia Menuju Kesiapan Tenaga Kerja Society 5.0 - Budiyono , Rokhmad; Fidyah Yuli Ernawati (Lembaga Pengembangan Kinerja Dosen, 2025)
The transition toward Society 5.0 demands a workforce capable of integrating technological proficiency with strong human-centered soft skills. This community engagement program aims to enhance the digital mindset and soft skills of PKK women in Boja District, Kendal Regency through a structured mentoring model rooted in human-centered learning principles. Using a needs assessment, experiential training sessions, and group mentoring, the program focused on increasing participants’ abilities in digital literacy, communication, collaboration, creativity, and community-based leadership. The mentoring activities revealed significant improvements in participants’ understanding of basic digital functions, such as the use of smartphones for communication, information access, and household economic opportunities. Engagement in interactive sessions—such as role play, guided discussions, and problem-solving simulations—strengthened participants’ confidence, interpersonal communication, and teamwork skills. Furthermore, several participants demonstrated emerging leadership abilities, particularly in facilitating peer learning and supporting other members during digital practice activities. These findings align with recent literature emphasizing the effectiveness of contextual digital training and experiential adult learning in promoting behavioral change and improving community readiness for technological transformation. Overall, the program successfully enhanced the participants’ readiness to face the challenges of Society 5.0 by fostering digital mindset growth, essential soft skills development, and strengthened leadership capacity. The results indicate that human-centered mentoring can serve as a sustainable approach to empowering local communities and improving their competitiveness in the digital era.